(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
As the most pristine and one of the biggest continents in the southern hemisphere, Antarctica has over the decade accumulated hydrocarbon pollution mainly due to human activities related to logistics and transportation in this area. Acetonitrile spills caused by the sinking of the cargo ships call for research into acetonitrile-degrading microorganisms in the form of bioremediation in order to be ready for disasters in the future. The efficiency of a previously isolated acetonitrile-degrading sludge consortium as a bioremediation technique has been demonstrated. However, as the acetonitrile concentration rises, its growth was severely restrained. Acetonitrile’s inhibitory effect on this consortium’s development rate is modeled in this work using the Luong, Aiba, Haldane, Hans-Levenspiel, Yano, Teissier and Monod models. Statistical evaluations indicated that the most suitable kinetic model to fit the growth rate on acetonitrile was the Teissier-Edwards’s model. The computed values for the Teissier constants like maximal reduction rate (max), half saturation constant for maximal degradation (Ks) and half inhibition constant (Ki) were 0.934 1/H (95% confidence interval 0.301 to 1.567), 1.504 g/L (95% confidence interval 0.877 to 2.131), and 4.574 g/L (95% confidence interval 2.764 to 6.383), respectively. The parameters obtained from this study will be beneficial in acetonitrile biodegradation works.